Natural graphite negative electrode material as well as negative electrode plate and lithium battery applying natural graphite negative electrode material

By controlling the particle size distribution of natural graphite negative electrode materials and setting the shell layer, the specific surface area is regulated, and the polarization and lithium evolution problems caused by excessive or too small particle size are solved, and efficient lithium ion transmission and long-term stable circulation performance are achieved.

CN119650631APending Publication Date: 2025-03-18CALB GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766822.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The particle size of natural graphite negative electrode materials will lead to too long lithium ion deintercalation path or increase surface defects, resulting in polarization, lithium evolution and interface side reactions, which will affect rate performance and cycling performance.

Method used

By controlling the particle size distribution of the natural graphite negative electrode material in the range of 8 μm to 20 μm, and a shell layer is provided on the surface of the natural graphite core to fill surface defects and adjust the specific surface area to make D50/BET>6.5 μm/(m2/g).

Benefits of technology

It realizes the lithium ion transmission effect under fast charging conditions, and maintains a stable structure and sufficient gram capacity after multiple cycles of charging and discharging, improving rate performance and cycling characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170880730000151
    Figure BDA0005170880730000151
  • Figure BDA0005170880730000161
    Figure BDA0005170880730000161
Patent Text Reader

Abstract

The invention provides a natural graphite negative electrode material as well as a negative electrode plate and a lithium battery applying the natural graphite negative electrode material. The natural graphite negative electrode material provided by the invention comprises a natural graphite inner core and a shell layer arranged outside the natural graphite inner core, the natural graphite negative electrode material simultaneously satisfies the following characteristics: 8 [mu] m < = D50 < = 20 [mu] m, 1 m < 2 > / g < = BET < = 3 m < 2 > / g, D50 / BETgt; and 6.5 [mu] m / (m < 2 > / g). The natural graphite negative electrode material provided by the invention has good rate capability, can still achieve the effect of smooth transmission of lithium ions under the working condition of quick charge, has good cycle characteristics, and can still keep the structure stable after long-time cycle charge and discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular, relates to a natural graphite negative electrode material and a negative electrode sheet and a lithium battery using the same. Background Art

[0002] Lithium batteries have been widely used in various portable electronic products and electric vehicles due to their high operating voltage, long cycle life, no memory effect, low self-discharge, and environmental friendliness. At present, natural graphite anode materials have become one of the mainstream lithium battery anode materials based on their excellent conductive properties.

[0003] The particle size of natural graphite negative electrode materials will affect the transmission path of lithium ions in the negative electrode. If the particle size of natural graphite negative electrode materials is too large, the path of lithium ions in the negative electrode will be too long, which is not conducive to the rapid deintercalation of lithium ions, and it is easy to produce polarization and lithium precipitation. In addition, the coating performance of large-particle-size negative electrode materials is poor, and it is easy to produce scratches during the coating process. The smaller the particle size of natural graphite negative electrode materials, the better the rate performance. However, small-particle-size negative electrode materials are prone to overpressure or powder loss during processing. In addition, as the particle size of natural graphite negative electrode materials decreases, the corresponding surface area increases. The surface of natural graphite materials often has uneven surface defects. The presence of these surface defects increases the interface of natural graphite materials exposed to the electrolyte, aggravates the interface side reactions between natural graphite materials and electrolytes, and accelerates the irreversible loss of natural graphite, thereby reducing the specific capacity of negative electrode active materials, reducing conductivity, and deteriorating rate performance and cycle performance. By setting a shell on the surface of natural graphite, the surface defects can be filled. However, if the shell is too thick, on the one hand, the gram capacity of the natural graphite negative electrode material will be significantly reduced. On the other hand, a too thick shell is also prone to form new (shell) surface defects, which will have an adverse effect on the storage stability and cycle stability of the natural negative electrode material. Summary of the invention

[0004] In order to achieve that the negative electrode active material has both good rate performance and good cycle performance, the present invention provides a natural graphite negative electrode material and a negative electrode sheet and a lithium battery using the same.

[0005] According to a first aspect of the present invention, a natural graphite negative electrode material is provided, which comprises a natural graphite core and a shell layer arranged outside the natural graphite core; the natural graphite negative electrode material simultaneously satisfies the following characteristics: 8μm≤D 50 ≤20μm, 1m 2 / g≤BET≤3m 2 / g,D 50 / BET>6.5μm / (m 2 / g). In order to make the natural graphite negative electrode material have good rate performance, the present invention controls the particle size distribution of the natural graphite negative electrode material within the range of 8μm to 20μm. In the above-mentioned natural graphite negative electrode material, the natural graphite core serves as the main gram capacity carrier of the natural graphite negative electrode material. Furthermore, a shell layer providing a coating effect is provided on the surface of the natural graphite core. The shell layer of the natural graphite negative electrode material can fill the surface defects of the natural graphite core, reduce the contact interface between the natural graphite core and the electrolyte in the electrochemical device based on it, and delay the loss of the natural graphite core during the application process. On the other hand, based on the adjustment of the shell layer, the specific surface area of ​​the natural graphite negative electrode material can be conveniently regulated. The present invention comprehensively considers the influence of the particle size distribution and specific surface area of ​​the natural graphite negative electrode material on its rate performance and cycle characteristics, so that the natural graphite negative electrode material meets D 50 / BET>6.5μm / (m 2 / g), so that the natural graphite negative electrode material provided by the present invention can maintain a smooth and efficient lithium ion transmission effect under fast charging working conditions, and can still maintain a stable structure and sufficient gram capacity after multiple cycles of charge and discharge. In summary, the natural graphite negative electrode material required by the present invention has both good rate performance and cycle characteristics. Based on the above advantages, the application of natural graphite negative electrode materials in lithium batteries is conducive to improving the rate performance and cycle characteristics of lithium batteries, which is conducive to the lithium battery maintaining a high level of energy density for a long time.

[0006] According to a second aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes a current collector and a negative electrode active coating disposed on a surface of the current collector. The negative electrode active coating includes the natural graphite negative electrode material as described above.

[0007] According to a third aspect of the present invention, a lithium battery is provided, comprising a positive electrode sheet and the negative electrode sheet described above.

[0008] The above-mentioned negative electrode sheet contains the natural graphite negative electrode material provided by the present invention. Based on the excellent electrochemical properties of the above-mentioned natural graphite negative electrode material, the battery product prepared by using the negative electrode sheet has good rate performance, good cycle performance and high battery energy density. DETAILED DESCRIPTION

[0009] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0010] According to a first aspect of the present invention, there is provided a natural graphite negative electrode material, which comprises a natural graphite core and a shell layer arranged outside the natural graphite core; the natural graphite negative electrode material simultaneously satisfies the following characteristics:

[0011] μm≤D 50 ≤20μm, 1m 2 / g≤BET≤3m 2 / g,D 50 / BET>6.5μm / (m 2 / g).

[0012] In order to make the natural graphite negative electrode material have good rate performance, the present invention controls the particle size distribution of the natural graphite negative electrode material within the range of 8μm to 20μm. In the above-mentioned natural graphite negative electrode material, the natural graphite core serves as the main gram capacity carrier of the natural graphite negative electrode material. Furthermore, a shell layer providing a coating effect is provided on the surface of the natural graphite core. The shell layer of the natural graphite negative electrode material can fill the surface defects of the natural graphite core, reduce the contact interface between the natural graphite core and the electrolyte in the electrochemical device based on it, and delay the loss of the natural graphite core during the application process. On the other hand, based on the adjustment of the shell layer, the specific surface area of ​​the natural graphite negative electrode material can be conveniently regulated. The present invention comprehensively considers the influence of the particle size distribution and specific surface area of ​​the natural graphite negative electrode material on its rate performance and cycle characteristics, so that the natural graphite negative electrode material meets D 50 / BET>6.5μm / (m 2 / g), so that the natural graphite negative electrode material provided by the present invention can maintain a smooth and efficient lithium ion transmission effect under fast charging working conditions, and can still maintain a stable structure and sufficient gram capacity after multiple cycles of charge and discharge. In summary, the natural graphite negative electrode material required by the present invention has both good rate performance and cycle characteristics. Based on the above advantages, the application of natural graphite negative electrode materials in lithium batteries is conducive to improving the rate performance and cycle characteristics of lithium batteries, which is conducive to the lithium battery maintaining a high level of energy density for a long time.

[0013] Preferably, the natural graphite negative electrode material satisfies 10 μm ≤ D 50 ≤18μm and 1m 2 / g≤BET≤1.5m 2 / g. The natural graphite negative electrode material having the above structure can achieve higher first efficiency and better cycle characteristics.

[0014] Preferably, the natural graphite negative electrode material includes a filling material, and the filling material fills the internal pores of the natural graphite kernel. In the natural graphite negative electrode material provided by the present invention, the above-mentioned natural graphite kernel is composed of natural graphite, and natural graphite often has abundant pores, so the interior of the natural graphite kernel formed by it will also have abundant pores, and the presence of these pores increases the interface where the natural graphite negative electrode material may contact the electrolyte, and the use of the filling material to fill the internal pores of the natural graphite kernel can avoid the electrolyte from entering the interior of the natural graphite kernel, reduce the interface side reaction between the natural graphite negative electrode material and the electrolyte, achieve the purpose of reducing the consumption of the electrolyte and reducing the consumption of active lithium, and help avoid the problems such as the cycle attenuation of the natural graphite negative electrode material.

[0015] Preferably, the material constituting the outer shell is used as the coating material, and the coating material and / or the filling material include an amorphous carbon material, and the amorphous carbon material is formed by carbonizing asphalt and / or resin.

[0016] Preferably, the asphalt includes at least one of coal-based asphalt and petroleum asphalt.

[0017] Preferably, the resin includes at least one of phenolic resin, epoxy resin, furan resin and furfural resin.

[0018] Preferably, the amorphous carbon material is obtained by carbonizing pitch.

[0019] Preferably, in the amorphous carbon material included in the natural graphite negative electrode material, the filling material includes the amorphous carbon material as the filled amorphous carbon, and the asphalt used to form the filled amorphous carbon satisfies the softening point of 150°C to 200°C and the coking value of 60% to 70%. The asphalt that meets the above softening point and coking value can show good fluidity in the process of forming the filled amorphous carbon, can fully penetrate into the internal pores of the natural graphite kernel, and the residual carbon rate of the amorphous carbon material converted by its carbonization is moderate, thereby ensuring that the internal pores of the natural graphite kernel are fully filled. If the softening point of the asphalt used is too high, its fluidity will deteriorate during the carbonization process. In addition, if the coking value of the asphalt used is too small, it will cause its residual carbon rate after carbonization to be low. The above situations are not conducive to the modification of the internal interface of the natural graphite kernel.

[0020] Preferably, the pitch used to form the filled amorphous carbon satisfies D 50 =1μm~4μm. The asphalt with a particle size within the above range is easily softened and converted into a fluid melt in the process of forming the filled amorphous carbon, which is conducive to the asphalt fully penetrating into the internal pores of the natural graphite core.

[0021] Preferably, the mass of the natural graphite core accounts for 40% to 80% of the total mass of the natural graphite negative electrode material, calculated by mass percentage. Based on the excellent conductive effect of natural graphite materials, by controlling the content of the natural graphite core in the natural graphite negative electrode material, the natural graphite negative electrode material can maintain a high level of gram capacity and good conductive properties.

[0022] According to a second aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes a current collector and a negative electrode active coating disposed on a surface of the current collector. The negative electrode active coating includes the natural graphite negative electrode material as described above.

[0023] According to a third aspect of the present invention, a lithium battery is provided, comprising a positive electrode sheet and the negative electrode sheet described above.

[0024] The above-mentioned negative electrode sheet contains the natural graphite negative electrode material provided by the present invention. Based on the excellent electrochemical properties of the above-mentioned natural graphite negative electrode material, the battery product prepared by using the negative electrode sheet has good fast charging performance, good cycle performance and high battery energy density.

[0025] Example 1

[0026] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50 =20.2μm, BET is 6.3m 2 / g, and the asphalt used has a softening point of 220℃, a coking value of 60%, and D 50 =3μm, in this embodiment, all the asphalt used is used as a coating material for forming a shell layer covering natural graphite, which is recorded as coated asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this embodiment according to the following operation:

[0027] S1. Take 10kg of natural graphite and 0.6kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0028] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0029] The natural graphite negative electrode material prepared in this embodiment has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The particle size test and BET specific surface area test of the natural graphite negative electrode material prepared in this embodiment are performed. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =20μm, BET=3m 2 / g.

[0030] Example 2

[0031] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50 =13.2μm, BET is 7.9m 2 / g, and the asphalt used has a softening point of 220℃, a coking value of 65%, and a 50 =3μm, in this embodiment, all the asphalt used is used as a coating material for forming a shell layer covering natural graphite, which is recorded as coated asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this embodiment according to the following operation:

[0032] S1. Take 10kg of natural graphite and 0.9kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0033] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0034] The natural graphite negative electrode material prepared in this embodiment has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The particle size test and BET specific surface area test of the natural graphite negative electrode material prepared in this embodiment are performed. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =13.5μm, BET=1.5m 2 / g.

[0035] Example 3

[0036] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50=19.8μm, BET is 6.7m 2 / g, and the asphalt used has a softening point of 180°C, a coking value of 65%, and a 50 =3μm, in this embodiment, all the asphalt used is used as the coating material for forming the shell layer of the natural graphite, which is recorded as the coating asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this embodiment according to the following operation:

[0037] S1. Take 10kg of natural graphite and 0.6kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0038] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0039] The natural graphite negative electrode material prepared in this embodiment has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The particle size test and BET specific surface area test of the natural graphite negative electrode material prepared in this embodiment are performed. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =20μm, BET=1m 2 / g.

[0040] Example 4

[0041] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50 =15.5μm, BET is 7.5m 2 / g, and the asphalt used has a softening point of 180°C, a coking value of 60%, and a D 50 =3μm, in this embodiment, all the asphalt used is used as the coating material for forming the shell layer of the natural graphite, which is recorded as the coating asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this embodiment according to the following operation:

[0042] S1. natural graphite is put into an isostatic pressing device, and the isostatic pressing device is used to mechanically extrude the natural graphite at an extrusion pressure of 200 MPa for 2 hours to obtain block graphite, and the block graphite is depolymerized and dispersed to obtain densified spherical graphite.

[0043] S2. Take 10 kg of densified spherical graphite and 0.6 kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50 Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0044] S3. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1250°C at a heating rate of 10°C / min, and maintained at 1250°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0045] The natural graphite negative electrode material prepared in this embodiment has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S3. The particle size test and BET specific surface area test of the natural graphite negative electrode material prepared in this embodiment are performed. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =15μm, BET=1.2m 2 / g.

[0046] Example 5

[0047] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50 =9.8μm, BET is 8.9m 2 / g, and the asphalt used includes two types: one of the asphalts, denoted as coated asphalt, is used to form a coating material for the shell layer covering natural graphite. The coated asphalt has a softening point of 220°C, a coking value of 60%, and a D 50 =3μm; another asphalt, recorded as filling asphalt, is used to form a filling material to fill the internal pores of natural graphite. The filling asphalt has a softening point of 180°C, a coking value of 60%, and a D 50 =1μm. The above raw materials were used to prepare the natural graphite negative electrode material of this embodiment according to the following operations:

[0048] S1. Put 10 kg of the above natural graphite and 0.5 kg of filling asphalt into an isostatic pressing device, heat the isostatic pressing device to 190° C., use the isostatic pressing device to mechanically extrude the above materials at an extrusion pressure of 180 MPa for 2 hours to obtain block graphite, and depolymerize and disperse the block graphite to obtain densified spherical graphite.

[0049] S2. Take 10.5 kg of densified spherical graphite and 0.4 kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50 Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0050] S3. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1250°C at a heating rate of 5°C / min, and maintained at 1250°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0051] The natural graphite negative electrode material prepared in this embodiment has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The internal pores of the natural graphite core are filled with a filling material, which is an amorphous carbon converted from the filling asphalt in the raw material after the high-temperature treatment of S3, and the coating material constituting the shell layer is an amorphous carbon carbonized from the coating asphalt in the raw material after the high-temperature treatment of S3. The particle size test and BET specific surface area test were performed on the natural graphite negative electrode material prepared in this embodiment. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =10μm, BET=1.5m 2 / g.

[0052] Example 6

[0053] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50 =17.7μm, BET is 7.1m 2 / g, and the asphalt used includes two types: one of the asphalts, denoted as coated asphalt, is used to form a coating material for the shell layer covering natural graphite. The coated asphalt has a softening point of 220°C, a coking value of 60%, and a D 50 =3μm; another asphalt, recorded as filling asphalt, is used to form a filling material to fill the internal pores of natural graphite. The filling asphalt has a softening point of 150°C, a coking value of 60%, and a D 50 =1μm. The above raw materials were used to prepare the natural graphite negative electrode material of this embodiment according to the following operations:

[0054] S1. Put 10kg of the above natural graphite and 0.5kg of filling asphalt into a mechanical fusion machine. Under a vacuum condition of -1MPa, heat the mechanical fusion machine to 180°C, stir continuously during the period, the stirring frequency is 25Hz, and the time is 24 hours. After completing the above operation, cool the mechanical fusion machine to room temperature and discharge the material to obtain pre-fused mixture I.

[0055] S2. Take 10.5 kg of pre-fused mixture I and 0.3 kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50 Hz and the fusion time is 4 hours. After the fusion is completed, discharge the material to obtain pre-fused mixture II.

[0056] S3. The pre-fused mixture II is placed in a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0057] The natural graphite negative electrode material prepared in this embodiment has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The internal pores of the natural graphite core are filled with a filling material, which is an amorphous carbon converted from the filling asphalt in the raw material after the high-temperature treatment of S3, and the coating material constituting the shell layer is an amorphous carbon carbonized from the coating asphalt in the raw material after the high-temperature treatment of S3. The particle size test and BET specific surface area test were performed on the natural graphite negative electrode material prepared in this embodiment. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =18μm, BET=1.3m 2 / g.

[0058] Comparative Example 1

[0059] The raw materials used to prepare the natural graphite negative electrode material in this comparative example include natural graphite and asphalt, wherein the natural graphite used has D 50 =6.2μm, BET is 10.2m 2 / g, and the asphalt used has a softening point of 150°C, a coking value of 55%, and a D 50 =4μm, in this comparative example, all the asphalt used is used as a coating material for forming a shell layer coating natural graphite, which is recorded as coated asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this comparative example according to the following operation:

[0060] S1. Take 10kg of natural graphite and 0.6kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0061] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0062] The natural graphite negative electrode material prepared in this comparative example has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The natural graphite negative electrode material prepared in this comparative example is subjected to a particle size test and a BET specific surface area test. The test results show that the particle size distribution of the natural graphite negative electrode material meets D 50 =6.5μm, BET=3.8m 2 / g.

[0063] Comparative Example 2

[0064] The raw materials used to prepare the natural graphite negative electrode material in this embodiment include natural graphite and asphalt, wherein the natural graphite used has D 50 =7.7μm, BET is 10.8m 2 / g, and the asphalt used has a softening point of 150°C, a coking value of 55%, and a D 50 =1μm, in this embodiment, all the asphalt used is used as a filling material for forming the internal pores of natural graphite, which is recorded as filling asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this embodiment according to the following operations:

[0065] S1. Put 10 kg of the above natural graphite and 0.5 kg of filling asphalt into an isostatic pressing device, heat the isostatic pressing device to 160° C., use the isostatic pressing device to mechanically extrude the above materials at an extrusion pressure of 180 MPa for 2 hours to obtain block graphite, and depolymerize and disperse the block graphite to obtain densified spherical graphite.

[0066] S2. 10.5 kg of densified spherical graphite was put into a carbonization furnace protected by nitrogen, and the temperature was increased to 1250°C at a heating rate of 5°C / min, and kept at 1250°C for 4 hours, then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material was obtained after being broken up and sieved.

[0067] The natural graphite negative electrode material prepared in this embodiment includes natural graphite and a filling material filling the internal pores of the natural graphite, and the filling material is amorphous carbon converted from the filling asphalt in the raw material after the high temperature treatment of S2. The particle size test and BET specific surface area test of the natural graphite negative electrode material prepared in this embodiment are performed. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =7.8μm, BET=4.2m 2 / g.

[0068] Comparative Example 3

[0069] The raw materials used to prepare the natural graphite negative electrode material in this comparative example include natural graphite and asphalt, wherein the natural graphite used has D 50 =23.9μm, BET is 6.2m 2 / g, and the asphalt used has a softening point of 150°C, a coking value of 55%, and a D 50 =4μm, in this comparative example, all the asphalt used is used as a coating material for forming a shell layer coating natural graphite, which is recorded as coated asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this comparative example according to the following operation:

[0070] S1. Take 10kg of natural graphite and 0.6kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0071] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0072] The natural graphite negative electrode material prepared in this comparative example has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The natural graphite negative electrode material prepared in this comparative example is subjected to a particle size test and a BET specific surface area test. The test results show that the particle size distribution of the natural graphite negative electrode material meets D 50 =24μm, BET = 0.7m 2 / g.

[0073] Comparative Example 4

[0074] The raw materials used to prepare the natural graphite negative electrode material in this comparative example include natural graphite and asphalt, wherein the natural graphite used has D 50 =6.1μm, BET is 9.8m 2 / g, and the asphalt used has a softening point of 220℃, a coking value of 65%, and D 50 =3μm, in this comparative example, all the asphalt used is used as a coating material for forming a shell layer coating natural graphite, which is recorded as coated asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this comparative example according to the following operation:

[0075] S1. Take 10kg of natural graphite and 1.1kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0076] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0077] The natural graphite negative electrode material prepared in this comparative example has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The natural graphite negative electrode material prepared in this comparative example is subjected to a particle size test and a BET specific surface area test. The test results show that the particle size distribution of the natural graphite negative electrode material meets D 50 =6.5μm, BET=2m 2 / g.

[0078] Comparative Example 5

[0079] The raw materials used to prepare the natural graphite negative electrode material in this comparative example include natural graphite and asphalt, wherein the natural graphite used has D 50 =17.8μm, BET is 7.1m 2 / g, and the asphalt used has a softening point of 150°C, a coking value of 55%, and a D 50 =1μm, in this comparative example, all the asphalt used is used as a coating material for forming a shell layer coating natural graphite, which is recorded as coated asphalt. The above raw materials are used to prepare the natural graphite negative electrode material of this comparative example according to the following operation:

[0080] S1. Take 10kg of natural graphite and 0.6kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50Hz and the fusion time is 4 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0081] S2. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1150°C at a heating rate of 10°C / min, and maintained at 1150°C for 4 hours, and then naturally cooled to room temperature and taken out, and the natural graphite negative electrode material is obtained after being broken up and sieved.

[0082] The natural graphite negative electrode material prepared in this comparative example has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The coating material constituting the shell layer is an amorphous carbon formed by carbonizing the coated asphalt in the raw material after the high temperature treatment of S2. The natural graphite negative electrode material prepared in this comparative example is subjected to a particle size test and a BET specific surface area test. The test results show that the particle size distribution of the natural graphite negative electrode material meets D 50 =18μm, BET=3.5m 2 / g.

[0083] Comparative Example 6

[0084] The raw materials used to prepare the natural graphite negative electrode material in this comparative example include natural graphite and asphalt, wherein the natural graphite used has D 50 =9.8μm, BET is 8.9m 2 / g, and the asphalt used includes two types: one of the asphalts, denoted as coated asphalt, is used to form a coating material for the shell layer covering natural graphite. The coated asphalt has a softening point of 250°C, a coking value of 65%, and a D 50 = 3μm; another asphalt, recorded as filling asphalt, is used to form a filling material to fill the internal pores of natural graphite. The filling asphalt has a softening point of 180°C, a coking value of 65%, and a D 50 =1μm features.

[0085] The above raw materials were used to prepare the natural graphite negative electrode material of this comparative example according to the following operation:

[0086] S1. Put 10 kg of the above natural graphite and 0.5 kg of filling asphalt into an isostatic pressing device, heat the isostatic pressing device to 190° C., use the isostatic pressing device to mechanically extrude the above materials at an extrusion pressure of 150 MPa for 2 hours to obtain block graphite, and depolymerize and disperse the block graphite to obtain densified spherical graphite.

[0087] S2. Take 10.5 kg of densified spherical graphite and 0.5 kg of coated asphalt and put them into a mechanical fusion machine with nitrogen protection for full fusion. The stirring frequency is 50 Hz and the fusion time is 2 hours. After the fusion is completed, the material is discharged to obtain a pre-fused mixture.

[0088] S3. The pre-fused mixture is put into a carbonization furnace protected by nitrogen, and the temperature is increased to 1250°C at a heating rate of 10°C / min, and then increased to 2200°C at a heating rate of 5°C / min, and maintained at 2200°C for 4 hours, and then naturally cooled to room temperature, taken out, and broken up and sieved to obtain natural graphite negative electrode material.

[0089] The natural graphite negative electrode material prepared in this comparative example has a core-shell structure, which includes a natural graphite core and a shell layer covering the natural graphite core. The internal pores of the natural graphite core are filled with a filling material, which is an amorphous carbon converted from the filling asphalt in the raw material after the high-temperature treatment of S3, and the coating material constituting the shell layer is an amorphous carbon carbonized from the coating asphalt in the raw material after the high-temperature treatment of S3. The natural graphite negative electrode material prepared in this comparative example was subjected to a particle size test and a BET specific surface area test. The test results show that the particle size distribution of the above natural graphite negative electrode material meets D 50 =10.4μm, BET=1.5m 2 / g.

[0090] Test Example 1

[0091] 1. Test object: The natural graphite negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were used as the test objects of this test example to perform a charge-off test.

[0092] Sample production method:

[0093] (1) Preparation of negative electrode

[0094] The natural graphite negative electrode material, conductive agent acetylene black, thickener CMC and binder SBR were mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water was added to the mixture, and the mixture was stirred until the system was uniform under the action of a vacuum stirrer to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on one surface of the negative electrode current collector copper foil, dried at room temperature, and then cold pressed and cut to obtain a ф14 mm negative electrode sheet to be tested.

[0095] (2) Preparation of electrolyte

[0096] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0097] (4) Preparation of isolation membrane

[0098] A polyethylene film is used as the separating film, and the polyethylene film is cut into small diaphragm circles of ф19mm.

[0099] (5) Preparation of button cells

[0100] Before assembly, the electrode sheet was dried in a vacuum box at -1.0 MPa and 80°C for 8 h, and the weight of the negative electrode sheet was weighed, and the mass of the active material on the negative electrode sheet was calculated. Subsequently, the membrane was transferred to the glove box and assembled into a button battery in the following order: negative electrode shell, gasket, lithium sheet, electrolyte, diaphragm, electrolyte, electrode sheet, positive electrode shell.

[0101] 3. Test method

[0102] At 25°C, the button cell made of the test natural graphite negative electrode material was tested according to the following procedure: stand for 12 hours, discharge to 5mV at a rate of 0.1C, stand for 10 minutes, discharge to 5mV at a rate of 0.05C, stand for 10 minutes, then discharge to 5mV at a rate of 0.01C, stand for 10 minutes, then discharge to 5mV at a current of 0.01mA, stand for 10 minutes, charge to 2V at a constant current of 0.1C, stand for 10 minutes, and end the test. The gram capacity and initial efficiency of the active substance were recorded.

[0103] The results of the power-off test are integrated into Table 1 of the present invention.

[0104] Example 7

[0105] The natural graphite negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were respectively used to prepare lithium batteries according to the following process steps.

[0106] 1. Preparation of positive electrode:

[0107] The positive electrode slurry is prepared according to the following method: the ternary positive electrode active material NCM333, the conductive agent acetylene black, and the binder PVDF are added into a vacuum mixer in a mass ratio of ternary positive electrode active material NCM333: conductive agent acetylene black: binder PVDF = 96:2:2 for mixing, and then the solvent NMP is added to the mixed slurry, and the mixed slurry is stirred until it is uniform under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment.

[0108] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled.

[0109] 2. Preparation of negative electrode sheet:

[0110] The negative electrode slurry was prepared as follows: the negative electrode active material, conductive agent acetylene black, thickener CMC, and binder SBR were added into a vacuum mixer in a mass ratio of natural graphite negative electrode material: conductive agent acetylene black: thickener CMC: binder SBR = 96.4:1:1.2:1.4 for mixing, and then deionized water was added as solvent to the mixture obtained, and the mixed slurry was stirred until it was uniform under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment.

[0111] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.

[0112] 3. Preparation of Electrolyte

[0113] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of EC:EMC:DEC=1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0114] 4. Selection of isolation film

[0115] In this embodiment, a polyethylene film is selected as the separator of the lithium battery.

[0116] 5. Assembly of lithium battery

[0117] The positive electrode sheet to be assembled, the isolation film, and the negative electrode sheet to be assembled are stacked in sequence, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and the bare battery cell is wound; the bare battery cell is placed in a battery casing, and after drying, the electrolyte is injected, and a lithium battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0118] Test Example 2

[0119] 1. Test object: The lithium battery prepared in Example 7 was used as the test object of this test example to conduct a battery performance test.

[0120] 2. Test items

[0121] (1) Storage performance test:

[0122] At 25°C, the test lithium battery was cycled according to the following procedure: fully charged at a 1C rate, and fully discharged until the capacity of the lithium battery was less than 80% of the initial capacity, and the number of cycles was recorded.

[0123] (2) Dynamic performance test:

[0124] At -10℃, the test lithium battery was fully charged at 0.2C and fully discharged at 0.33C for 10 times, and then fully charged at 0.2C, and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, the area of ​​lithium deposition on the surface of the negative electrode is 5% to 10%, which is considered to be slight lithium deposition, the area of ​​lithium deposition on the surface of the negative electrode is 10% to 50%, which is considered to be moderate lithium deposition, and the area of ​​lithium deposition on the surface of the negative electrode is greater than 50%, which is considered to be severe lithium deposition.

[0125] 3. Test results

[0126] The performance test results of the participating lithium batteries and the specific conditions of the negative electrode active materials used in the lithium batteries are shown in Table 1.

[0127] Table 1. Performance index test results

[0128]

[0129]

[0130] It can be clearly seen from the test results shown in Table 1 that the lithium batteries made of the natural graphite negative electrode materials provided in Examples 1 to 6 can maintain good capacity during multiple cycles of charge and discharge during the test process, and have good cycle characteristics. Compared with the natural graphite negative electrode materials provided in Examples 1 to 6, the lithium batteries made of the natural graphite negative electrode materials provided in Comparative Examples 1 to 5 have significantly fewer cycles measured under the test conditions of Test Example 2, that is, the cycle characteristics of the lithium batteries made of the natural graphite negative electrode materials provided in Comparative Examples 1 to 5 are significantly poor, wherein the lithium battery made of the negative electrode active material of Comparative Example 3 has serious lithium precipitation on its negative electrode sheet after the cycle charge and discharge test. In addition, although the natural graphite negative electrode material provided in Comparative Example 6 has a relatively high number of cycles measured in the cycle performance test of this test example, Comparative Example 6 has a precipitation situation in the rate performance test, and its corresponding first efficiency of the power-down test is low.

[0131] In Comparative Example 1 and Comparative Example 4, the particle size of the natural graphite raw material used is relatively small, resulting in a small particle size of the prepared natural graphite negative electrode material. The negative electrode sheet prepared using the natural graphite negative electrode material is prone to powder loss during use, resulting in poor structural stability of the negative electrode sheet. Therefore, from the test result data shown in Table 1, it can be seen that the number of cycles of the lithium batteries prepared using the natural graphite negative electrode materials provided in Comparative Example 1 and Comparative Example 4 is significantly low. In particular, in the process of preparing the natural graphite negative electrode material in Comparative Example 1, the softening point and coking value of the coated asphalt used to construct the shell layer are relatively low, but the particle size is relatively large. Therefore, the amorphous carbon formed by carbonization of the coated asphalt has a poor coating effect on the small-particle natural graphite core, so that the BET of the natural graphite negative electrode material finally obtained is relatively large, and there are many defects on its surface and bulk phase. It is easy to have side reactions with the electrolyte during the charge and discharge process, so the initial efficiency is low. In addition, during the process of cyclic charge and discharge of the natural graphite negative electrode material, as the cycle proceeds, the SEI film on the interface of the natural graphite negative electrode material continues to thicken, and the cycle performance deteriorates. On the other hand, due to the low particle size of the negative electrode active material obtained in the comparative example, the corresponding gram capacity is also reduced. Similar to Comparative Example 1, in Comparative Example 5, the softening point and coking value of the coating asphalt used to construct the shell layer of the natural graphite negative electrode material are relatively low. Even if the particle size of the natural graphite raw material used is relatively large, the coating effect of the coating asphalt on the natural graphite inner core is still poor, resulting in the BET of the natural graphite negative electrode material finally obtained being relatively large. The cycle performance of the lithium battery made using the natural graphite negative electrode material provided in Comparative Example 5 is also relatively poor.

[0132] In the process of preparing the natural graphite negative electrode material in Comparative Example 2, the natural graphite is not externally coated and modified. Even though the natural graphite has been densely filled to reduce the internal pore interface of the natural graphite to a certain extent, there are still a large number of defects on the surface of the natural graphite, resulting in a large BET of the natural graphite negative electrode material. The natural graphite negative electrode material is prone to side reactions such as solvent co-embedding with the electrolyte during battery operation, and the initial efficiency is low. Moreover, as the cycle proceeds, the SEI film on the interface of the natural graphite negative electrode material continues to thicken, and the cycle performance deteriorates.

[0133] Compared with Example 1, the particle size of the natural graphite raw material selected in Comparative Example 3 is larger, so that the particle size of the obtained natural graphite negative electrode material is larger and the BET is lower, resulting in a longer lithium insertion channel of the natural graphite negative electrode material, so the lithium battery prepared thereby has poor kinetic performance and is prone to lithium precipitation. In addition, due to the large particle size of the natural graphite negative electrode material, during the cyclic charge and discharge process, the natural graphite negative electrode material produces obvious expansion stress, resulting in uneven internal stress distribution of the negative electrode sheet, and the local expansion stress easily causes the natural graphite structure to collapse, resulting in deterioration of the cycle performance. The above reasons lead to the cycle performance of the battery corresponding to Comparative Example 3 being significantly worse than the battery cycle performance corresponding to other embodiments.

[0134] The natural graphite negative electrode materials provided in Example 5 and Comparative Example 6 are compared, and both satisfy 8 μm ≤ D 50 ≤20μm and 1m 2 / g≤BET≤3m 2 / g, but the two are different in whether they satisfy D 50 / BET>6.5μm / (m 2 / g) constitutes a difference, the former meets this feature, while the latter does not meet this feature. From the data shown in Table 1, it can be seen that the number of cycles measured by the natural graphite negative electrode material of Comparative Example 6 is significantly lower than the number of cycles measured by the natural graphite negative electrode material of Example 5. The above comparison results of Example 5 and Comparative Example 6 illustrate that the particle size distribution and specific surface area of ​​the natural graphite negative electrode material are comprehensively regulated to make the natural graphite negative electrode material meet D 50 / BET>6.5μm / (m 2 / g), which is beneficial to improve the cycle characteristics of natural graphite negative electrode materials. In addition, based on the natural graphite negative electrode material provided in Comparative Example 6, the first efficiency of the buckle test measured in this test example is low, and the test results of the fast charge experiment analysis show that by making the natural graphite negative electrode material meet D 50 / BET>6.5μm / (m 2 / g), and can also improve the initial efficiency of natural graphite negative electrode materials and the lithium ion kinetic transmission efficiency.

[0135] The natural graphite negative electrode materials prepared in Examples 1 to 6 all satisfy: 8 μm ≤ D 50 ≤20μm、1m 2 / g≤BET≤3m 2 / g,D 50 / BET>6.5μm / (m 2 Based on the test results of this test example, the lithium batteries using Examples 1 to 6 can have sufficient capacity, good rate performance and good cycle performance.

[0136] According to the multiple test indicators of this test example, the lithium battery prepared by using the natural graphite negative electrode material of Example 2, Example 4, Example 5, and Example 6 can better balance the initial efficiency and cycle characteristics. In Example 4, in the process of preparing the natural graphite negative electrode material, the natural graphite is subjected to mechanical densification treatment, thereby reducing the internal pores of the natural graphite. As a result, after the natural graphite negative electrode material is applied to the lithium battery, the electrolyte in the lithium battery is difficult to enter the interior of the natural graphite negative electrode material, which can reduce the interface side reaction between the natural graphite negative electrode material and the electrolyte to a certain extent. In the process of preparing the natural graphite negative electrode material, both Example 5 and Example 6 involve the application of filling asphalt. After carbonization treatment, the amorphous carbon converted from the filling asphalt fills the internal pores of the natural graphite kernel, which can effectively reduce the internal pore interface of the natural graphite kernel and reduce the interface side reaction between the natural graphite negative electrode material and the electrolyte during the application process, so that the lithium batteries prepared in Example 5 and Example 6 respectively have excellent cycle characteristics.

[0137] Comparing the natural graphite negative electrode materials prepared in Example 1 and Example 3, respectively, the particle size distributions of the two are similar, both reaching about 20 μm, while the specific surface area of ​​the natural graphite negative electrode material in Example 1 is higher, and the corresponding first efficiency of the power-off test is lower. Except for Example 3, compared with the natural graphite negative electrode materials in other examples, the first efficiency of the power-off test measured by the natural graphite negative electrode material provided in Example 1 is also at a lower level. The above test results show that in the natural graphite negative electrode materials prepared in Examples 1 to 6, the specific surface area of ​​the natural graphite negative electrode material is further made to meet 1m 2 / g≤BET≤1.5m 2 / g, which is beneficial to improve the initial efficiency of the lithium battery based thereon. Further, the test results corresponding to Example 3 are compared with the test results corresponding to Examples 2, 4, 5, and 6, respectively. The number of cycles measured for the natural graphite negative electrode material of Example 3 is relatively small, which indicates that in the natural graphite negative electrode material provided in the above examples, the particle size distribution of the natural graphite negative electrode material is controlled within 10 μm ≤ D 50 ≤18μm, which is beneficial to improving the cycle characteristics of lithium batteries based on it.

[0138] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A natural graphite negative electrode material, characterized in that: It comprises a natural graphite core and a shell layer arranged outside the natural graphite core; the natural graphite negative electrode material satisfies the following characteristics at the same time: 8μm≤D 50 ≤20μm, 1m 2 / g≤BET≤3m 2 / g,D 50 / BET>6.5μm / (m 2 / g).

2. The natural graphite negative electrode material according to claim 1, characterized in that: The natural graphite negative electrode material satisfies 10 μm≤D 50 ≤18μm and 1m 2 / g≤BET≤1.5m 2 / g.

3. The natural graphite negative electrode material according to claim 1, characterized in that: The natural graphite negative electrode material includes a filling substance, and the filling substance fills the internal pores of the natural graphite core.

4. The natural graphite negative electrode material according to claim 3, characterized in that: The material constituting the shell is used as a coating material, and the coating material and / or the filling material include an amorphous carbon material, and the amorphous carbon material is formed by carbonizing asphalt and / or resin.

5. The natural graphite negative electrode material according to claim 4, characterized in that: The amorphous carbon material is formed by carbonizing pitch.

6. The natural graphite negative electrode material according to claim 5, characterized in that: In the amorphous carbon material included in the natural graphite negative electrode material, the filling substance includes the amorphous carbon material as filled amorphous carbon, and the asphalt used to form the filled amorphous carbon satisfies a softening point of 150° C. to 200° C. and a coking value of 60% to 70%.

7. The natural graphite negative electrode material according to claim 6, characterized in that: The pitch used to form the filled amorphous carbon satisfies D 50 =1μm~4μm.

8. The natural graphite negative electrode material according to any one of claims 1 to 7, characterized in that: Calculated by mass percentage, the mass of the natural graphite inner core accounts for 40% to 80% of the total mass of the natural graphite negative electrode material.

9. A negative electrode sheet, characterized in that: The invention comprises a current collector and a negative electrode active coating arranged on the surface of the current collector, wherein the negative electrode active coating comprises the natural graphite negative electrode material according to any one of claims 1 to 8.

10. A lithium battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet as claimed in claim 9.